Inventory Management and Logistics Cost Reduction: A Case of a Malaysia Herbal Medicine Company - Fadilah, Siali; Liu, Yao; Cheng, Jack Kie (Scientific Research, 2013)
Nowadays many studies have stressed the diagnosing inventory systems. This article examined problems encountered on logistics in a Malaysia herbal medicine company. The diagnosis was conducted using the fish bone diagram for the whole supply chain process from the production, hub warehouse, freight forwarders, zone warehouse to customers. The derived results highlight the inventory level management as the root reason, which leads to a set of initial recommenda- tions, including: 1) install the computer-based software system to control inventory level which is to be integrated with the supply chain; and 2) meanwhile implement aggressive marketing approaches to minimize the rate of the returned products.